THE CORRELATION BETWEEN COVID-19 KNOWLEDGE AND COMMUNITY ANXIETY AND DEPRESSION IN INDONESIA’S RED ZONE DURING THE PANDEMIC - Prakoso, Denny Anggoro; Dewi, Anis Prima; Azzahra, Anindya Faradila (Indonesian Journal for Health Sciences, 2025)
The rapid spread of Covid-19 has impacted physical and psychological well-being globally, including in Indonesia. Anxiety and depression are prevalent psychological challenges during the pandemic. This study aimed to assess the relationship between Covid-19 knowledge and psychological outcomes—anxiety and depression—among residents in Indonesia's high-risk "red zones." A cross-sectional design was employed, involving 394 respondents who met inclusion criteria, selected through convenience sampling. Data were collected using online surveys incorporating the Knowledge, Attitude, and Practice (KAP), GAD-7, and PHQ-9 questionnaires. Results indicated that 84.5% of respondents had good knowledge of Covid-19. However, 35.3% and 27.9% reported depression and anxiety, respectively. Spearman correlation analysis found no significant relationship between Covid-19 knowledge and either anxiety (p = 0.311) or depression (p = 0.356). These findings suggest that while knowledge levels were high, psychological issues persisted, highlighting a gap in addressing mental health during the pandemic. This study underscores the need for targeted interventions to mitigate the psychological impact of Covid-19 in high-risk communities